Mainstreaming Climate Smart Agriculture (CSA) and Climate Information Service (CIS) into Universities’ Curricula: Capacity Building of Stakeholders on Three Thematic Modules in West African Countries - Amponsah, William; Agyare, Wilson Agyei; Sorho, Fatogoma; Lamptey, Benjamin; Segnon, Alcade Christel; Zougmore, Robert Bellarmin; Kone, Daouda (2025)
The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) Project builds on the initiatives and achievements under the CGIAR research programme on Climate Change, Agriculture and Food Security (CCAFS) in Africa. The West African Science Service Centre on Climate Change and Adapted Land Use (WASCAL) is working with the Regional Universities Forum for Capacity Building in Agriculture (RUFORUM) to build capacities of university lecturers in climate-smart agriculture (CSA) technologies and climate information services (CIS). WASCAL has developed curricula in three thematic modules, which includes (i) Soil Carbon Sequestration and Crop Production, (ii) Disaster Risk Management in Crops, Livestock and Aquaculture and (iii) Pest and Disease Management in Agriculture under Climate Change. This report elaborate on training workshops organised in Ghana, Mali and Burkina Faso, discussing the key observations, lessons learnt and relevant recommendations. The workshops university management and in-person training of 324 participants with 26% female from 12 African Countries. Participants were enthused and expressed their immense gratitude for the opportunity to partake in the training programme through their contributions and queries to the presentations and also providing capacity building for lecturers regarding CSA and CIS. Participants were urged to be more proactive and extend information/education received at the workshops to their colleagues for an all-inclusive knowledge sharing and support movement groups interested in incorporating CSA and CIS into University Curricula. The training workshop also encouraged the involvement and participation of women in discussions and bring them on-board to partake in high-level dialogue processes. A key lesson learnt was for the need to develop a detailed manual for all practical sessions of the modules, especially, with practical case studies peculiar to or practiced by the AICCRA Project Thematic Countries (Ghana, Mali, and Senegal).